Correspondance formelle dans le roman Le ventre de Paris en français et The belly of Paris en indonésien - Dita Arinda Chintia Dewi; Dies Oktavia Dwi Astuti (Universitas Negeri Semarang, 2024)
This research aims to describe the formal correspondence in the novel Le Ventre de Paris in French and The Belly of Paris in Indonesian. This is qualitative descriptive research. The theory used to analyze the data is the formal correspondence theory proposed by Catford. The data sources for this research are the novels “Le Ventre de Paris” in French and “The Belly of Paris” in Indonesian. The data are all propositions that have a formal correspondence in the novels “Le Ventre de Paris” and “The Belly of Paris.” The results show that 93 propositions are the subject of a formal match. Thirty-five propositions have formal correspondence based on word classes. Nine propositions have formal correspondence based on linguistic structures.